Morocco’s Distinctive Islam at a Crossroads: The State’s Support for Sufism - Faitour, Mouad (Religions, 2024)
In the aftermath of the 2003 Casablanca bombings, the Moroccan state emphasized, through official public discourse, the components that constitute “official Moroccan Islam” to combat extremist ideologies. These religious elements include Mālikism in jurisprudence, Ashʿarism in theology, and the Sufism of Imam Al-Junayd (d. 298/910), all balanced by the pledge of allegiance to King Mohammed VI (a descendant of the Sharifian lineage), the constitutionally designated Commander of the Faithful and sole religious leader. Since the reform policy initiated in 2004, the Moroccan state has constructed a narrative on the distinctiveness of Moroccan Islam—moderate and tolerant—and promoted it among its own citizens and beyond its borders. However, while the Moroccan state claims to have a unique form of Islam, controversial arguments have been raised questioning the nature of the state’s purported Islam. Other criticisms include investigating the state’s endorsement of Sufism and its broader policy of institutionalization. Yet, this article argues that the state supports any form of Islam, not necessarily Sufism, that aligns with its religious and political leadership. Like other Arab and Muslim states, Morocco’s religious policy is impacted by the global context, where Salafism is now perceived as a threat to established worldviews. In addition, this article argues that Morocco’s support for Sufi Islam is based not merely on its perceived political passivity, but because it complements the state’s policies and gains advantages from this support. It concludes that the official narrative of Moroccan Islam, which emphasizes a Sufi-oriented approach to counter extremism, is open to question, particularly given that Salafism was the state’s preferred form of Islam in post-colonial Morocco. This highlights the complex and often conflicting relationship between political actors and religious leaders in shaping Morocco’s religious discourse.